2017
DOI: 10.4236/wjcd.2017.75016
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Profile of Coronary Artery Disease in Diabetic Patients with Acute Coronary Syndrome: Results of the Saudi Coronary Athero-Thrombotic Disease (SAUDICAT)

Abstract: Cardiovascular disease is the leading cause of mortality in patients with diabetes mellitus (DM). We sought to establish for the first time in Saudi Arabia an intravascular ultrasound (IVUS) profile of DM patients with acute coronary syndrome (ACS). Patients and methods: We retrospectively analyzed 210 IVUS studies in 181 patients hospitalized in King Salman Heart Centre for ACS. IVUS was performed to guide percutaneous coronary interventions (PCI) of borderline moderate lesions. Results: Mean age was 58 ± 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Lawand et al 19 demonstrated longer lesions and increased plaque volumes in diabetic patients admitted with acute coronary syndrome as compared to non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lawand et al 19 demonstrated longer lesions and increased plaque volumes in diabetic patients admitted with acute coronary syndrome as compared to non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%